DeDePro Wireless Intruder Detection System (WIDS) against de-authentication/ disassociation attacks in 802.11 A/B/G/N / Norzaidi Baharudin - Baharudin, Norzaidi (2014)
Wireless network is always being a target from the various kinds of attacks. Many kind of security mechanism were introduced, such as WEP, WPA and WPA2. However, this security mechanism is only to protect the network from the outside access. Those security mechanisms are not handle of the security and protection of the wireless clients that are vulnerable to the internal attacks such as contributed by the weakness of management frames on 802.11a/b/g/n. The management frames on 802.11a/b/g/n are sent unencrypted with a plain text, thus it can be spoof and forge by anybody on the area of the wireless proximity. Even though they was introduced the 802.11w that will protect the management frames but there are still lot of legacy wireless devices been used and not supported with 802.11w. The objective of this research is to propose a new kind of tools that can be use as a personal WIDS (Wireless Intruder Detection System). Furthermore, this research will introduce the detection mechanism of the de-authentication / disassociation attacks on current 802.11a/b/g/n. Finally, the result and analysis will be present and to show the effectiveness of the propose scheme.